Sprostowanie danych osobowych po zmianie płci – glosa do wyroku Trybunału Sprawiedliwości z dnia 13 marca 2025 r. w sprawie C-247/23 Deldits - Matusiak-Frącczak, Magdalena (PRAWO i WIĘŹ, 2026)
The Court of Justice in Case C-247/23 Deldits ruled that a person’s gender is personal data, and transgender people have the right to request that the controller correct their gender marker under Article 16 GDPR. The transgender person will bear the burden of proof of gender change, but the controller cannot request evidence of having undergone gender reassignment surgery. As will be shown in the paper, such an interpretation is consistent with European Union law and the requirements of the European Convention on Human Rights. Polish practice also does not require evidence of having undergone gender reassignment surgery by a transgender person. The procedure under Article 16 of the GDPR will operate alongside the court procedure for determining gender and will facilitate the daily functioning of transgender people.